Family Fun and Togetherness : How to make your home a place where children enjoy living. - Rickerson, Wayne (Victor Books, 1979)
A very nice copy of the book, "Family Fun and Togetherness" with the Textbook and Leaders Guide by Wayne Rickerson. How to make your home a place where children enjoy living. Interesting alternatives, based on the Bible, to keep your family enjoying each other and having good times together. 132 pages in the textbook and 43 pages in the Leaders guide.